School climate and its relationship to the values of students in the city high schools in the Bicol region - Dancel, Ophelia Mumpar (1984)
The study was conducted in 24 selected high schools in the cities of Legazpi, Naga and Iriga with 906 students accomplishing a three-part researcher-made questionnaire. School climate is generally supportive in more public schools than private schools. School climate promotes more terminal values than instrumental values and more values oriented to self rather than to society. Student needs have more influence on student values than environment press while school environment press factors affect more terminal values than instrumental values.
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: Values; High school students -- Philippines -- Bicol Region; School environment